2011
DOI: 10.1245/s10434-011-1710-7
|View full text |Cite
|
Sign up to set email alerts
|

SPIO-Enhanced Magnetic Resonance Imaging for the Detection of Metastases in Sentinel Nodes Localized by Computed Tomography Lymphography in Patients with Breast Cancer

Abstract: SPIO-enhanced MR imaging is a useful method of detecting metastases in sentinel nodes localized by CT-LG in patients with breast cancer and may avoid sentinel node biopsy when the sentinel node is diagnosed as disease-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 37 publications
0
63
0
Order By: Relevance
“…A CT scan was performed after massaging the iodinated contrast agent injection site. SPIO (a 40-µL aliquot of Resovist, containing 1.115 mg iron, diluted in 20 mL normal saline, as per Motomura et al, (53) was administered locally, similar to the administration of dye and radioisotope during sentinel node detection. The injection sites of SPIO were gently massaged for 1 min.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
See 2 more Smart Citations
“…A CT scan was performed after massaging the iodinated contrast agent injection site. SPIO (a 40-µL aliquot of Resovist, containing 1.115 mg iron, diluted in 20 mL normal saline, as per Motomura et al, (53) was administered locally, similar to the administration of dye and radioisotope during sentinel node detection. The injection sites of SPIO were gently massaged for 1 min.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
“…In the series of 102 patients with breast cancer and clinically negative nodes, Motomura et al (53) reported the mean number of sentinel nodes identified by CT lymphography was 1.1 (range, 1-3). The sensitivity, specificity, and accuracy of 1.5T MRI for the diagnosis of sentinel node metastases were 84.0%, 90.9%, and 89.2%, respectively.…”
Section: Sentinel Lymph Node Detection With Spio (Interstitial Mr Lymmentioning
confidence: 99%
See 1 more Smart Citation
“…They have demonstrated that the sensitivity, specificity and overall accuracy of SPIO-enhanced MRI make it a useful method for detecting SLN metastases. In a study on 102 patients with breast cancer the sensitivity, specificity, and accuracy of SPIO-enhanced MRI for the detection of SLN metastases were at 84.0, 90.9, and 89.2 %, respectively [26]. In a direct comparison between conventional MRI and SPIO-enhanced MRI, it was found that SPIO-enhancement was superior in terms of sensitivity, specificity and overall accuracy [25].…”
Section: The Role Of Mnps In Diagnosis Of Metastatic Lymph Node Spreadmentioning
confidence: 99%
“…The use of MNPs as MRI contrast agents provides a non-invasive method of imaging the complete lymphatic drainage basin from the tumour. This imaging subsequently allows visualization of any clinically positive lymph nodes and precise identification of their location [25,26].…”
Section: The Role Of Mnps In Diagnosis Of Metastatic Lymph Node Spreadmentioning
confidence: 99%